Weight Changes in Hormonal Contraceptive Users at Rosmiati Independent Practice in Palopo City - Asmawati, Asmawati (International Journal of Public Health Excellence (IJPHE), 2025)
Background: Hormonal contraception refers to contraceptive methods that aim to prevent pregnancy using agents possessing estrogen and progesterone. This study aimed to determine the effect of hormonal contraceptive use on changes in body weight among acceptors at Praktik Mandiri Bidan Rosmiati, Palopo City. Methods: This was an analytical observational study using a retrospective cohort approach. The total population of injectable contraceptive users was 445. A purposive sampling technique was employed, with a case-to-control ratio 1:1, resulting in 208 cases and 208 controls. The study was conducted at Praktik Mandiri Bidan Rosmiati, Palopo City, in 2024. Results: Based on age distribution, among the 208 case participants, 189 (90.9%) were under 35, while in the control group, 169 (81.3%) were under 35. Regarding the duration of use, 145 participants (69.7%) in the case group and 155 participants (74.5%) in the control group had used hormonal contraception for more than two years. Statistical analysis using odds ratio showed that both age and duration of use significantly influenced body weight changes among hormonal contraceptive acceptors at the study site. Conclusion: The majority of hormonal contraceptive acceptors experienced changes in body weight following long-term use. Age and duration of contraceptive use were significant factors, with those under the age of 35 having a higher risk of experiencing weight changes compared to older users. Keywords: Acceptors, Hormonal Contraception, Body Weight